2017
DOI: 10.1007/s12602-017-9333-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin B12, Lactate Dehydrogenase, and Regulation of NF-κB in the Mitigation of Sodium Arsenite-Induced ROS Generation in Uterine Tissue by Commercially Available Probiotics

Abstract: Managing arsenic intoxication with conventional metal chelators is a global challenge. The present study demonstrated the therapeutic role of probiotics against arsenic-induced oxidative stress and female reproductive dysfunction. Sodium arsenite-treated (1.0 mg/100 g body weight) Wistar female rats were followed up by a post-treatment of commercially available probiotic mixture in powder form (0.25 mg/100 g body weight) orally. Rats that experienced arsenic ingestion showed a significant lessening in the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 103 publications
1
4
0
Order By: Relevance
“…The intracellular antioxidant enzymatic activity in female reproductive organs was reduced by the excessive ROS production caused by the arsenic intoxication. These results consistent with previous findings 24 . Electrozymographic impression revealed that, the treatment of AA (1.0 mg / 100gm body weight) and vitamin B 12 (0.09 μg / 100gm body weight) alone or jointly in arsenic ingested rats protected the uterine and ovarian antioxidant enzymatic activities (SOD, catalase, and GPx) due to its probable own intrinsic antioxidant properties Fig.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The intracellular antioxidant enzymatic activity in female reproductive organs was reduced by the excessive ROS production caused by the arsenic intoxication. These results consistent with previous findings 24 . Electrozymographic impression revealed that, the treatment of AA (1.0 mg / 100gm body weight) and vitamin B 12 (0.09 μg / 100gm body weight) alone or jointly in arsenic ingested rats protected the uterine and ovarian antioxidant enzymatic activities (SOD, catalase, and GPx) due to its probable own intrinsic antioxidant properties Fig.…”
Section: Discussionsupporting
confidence: 94%
“…To identify the nature of the follicles the diameter of each follicle was measured and quantifies the number of follicles in different stages of folliculogenesis in each ovary 24 . The follicles were categorized as small preantral follicles (SPAF), large preantral follicles (LPAF), small antral follicles (SAF), medium antral follicles (MAF), large antral follicles (LAF), graafian follicles on the basis of their morphology and diameter and the numbers of regressive follicles (RF) were counted.…”
Section: Ovarian and Uterine Histopathologymentioning
confidence: 99%
“…Since the production of reactive oxygen species is high in reproductive tissue due to active metabolism and steroidogenesis, the tissue is under continuous oxidative stress. The result of the present investigation demonstrated the adverse effect of arsenic treatment on female gonadal steroidogenesis and antioxidant defense mechanism 29 . In ovarian steroidogenesis 3 and 17 -HSDs are the key regulatory enzymes, the suppressed activities of these enzymes along with elevated cholesterol levels by arsenic suggest alteration in its hormone synthesis 27,30,31 .…”
Section: Resultsmentioning
confidence: 53%
“…Administration of L. plantarum CCFM8610 reversed all of the reductions of mRNA expression of tight-junction proteins (ZO-1, ZO-2, occludin, and claudin-1) caused by Cd exposure, decreased intestinal permeability and reduced Cd leakage into systemic circulation [50]. Preventing systemic absorption of HMs by probiotics thus leads to alleviation of oxidative stress in various tissues and consequent mitigation of tissue damages as reported [100,101,102]. For example, co-treatment of L. plantarum CCFM8610 and Cd cause a decreased production of metallothionein and downregulation expression of genes in the mitogen-activated protein kinases (MAPK) pathways in the liver [19].…”
Section: Probiotics As a Potential Tool In Contaminants Remediationmentioning
confidence: 97%